PENGARUH PENDAPATAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. AROMADUTA RASAPRIMA - Ni Nyoman Ayu Krisna; Ni Made Widani; I Kadek Widhiantara (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to determine the effect of income and motivation on employee performance at PT. Aromaduta Rasaprima. A quantitative approach was employed with a total of 40 respondents. The data analysis techniques used include classical assumption tests, multiple linear regression analysis, correlation tests, and the coefficient of determination. The results show that partially, income (X1) has a significant effect on employee performance (Y) with a significance value of 0.001 and a regression coefficient of 0.144. Similarly, motivation (X2) has a positive and significant effect on employee performance with a significance value of 0.001 and a regression coefficient of 0.234. Simultaneously, income and motivation have a significant effect on employee performance, as indicated by a significance value of 0.001. The Adjusted R Square value of 0.579 indicates that 57.9% of the variation in employee performance is explained by income and motivation, while the remaining 42.1% is influenced by other factors outside the scope of this study. In conclusion, increased income and work motivation can significantly boost employee performance. Therefore, companies are advised to implement policies that strengthen these two factors to improve overall productivity.